IMPLEMENTASI NILAI-NILAI PENDIDIKAN KARAKTER PADA K13 DALAM PAI DAN BUDI PEKERTI DI SMP ISLAM AL AMJAD MEDAN SUNGGAL - Zularwan Al Rasyidin, Ali Imran Sinaga (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: This research is intended to answer the problem: What are the values of education character in Islamic Education (PAI) in grade VII of Islamic Junior High School Al Amjad Medan? How to apply character education in Islamic Education PAI in class VII of Islamic Junior High School Al Amjad Medan? What are the problems of application of education character in Islamic Education (PAI) in grade VII of Islamic Junior High School Al Amjad Medan? The application of education character in PAI at Islamic Junior High School Al Amjad Medan uses two ways, namely learning activities at school and outside school. in the learning activities in the school educators put forward the methods of teaching, exemplary, and reflection that exist in the material PAI class VII through the approach of learning model with the principle of Contextual Teaching and Learning. Then evaluation evaluation of character education in PAI at Islamic Junior High School Al Amjad Medan covers: input, process, output, and outcomes. Input implementation (students and teachers).Penelitian ini dimaksudkan untuk menjawab permasalahan: Apa saja nilai-nilai pendidikan karakter dalam PAI di kelas VII SMP Islam Al Amjad Medan? Bagaimana Penerapan pendidikan karakter dalam PAI di kelas VII SMP Islam Al Amjad Medan? Apa saja problematika Penerapan pendidikan karakter dalam PAI di kelas VII SMP Islam Al Amjad Medan? Penerapan pendidikan karakter dalam PAI di SMP Islam Al Amjad Medan menggunakan dua cara, yakni kegiatan pembelajaran di sekolah dan di luar sekolah. Dalam kegiatan pembelajaran di sekolah pendidik mengedepankan metode pengajaran, keteladanan, dan refleksi yang ada dalam materi PAI kelas VII melalui pendekatan model pembelajaran dengan prinsip prinsip Contextual Teaching and Learning. Kemudian evaluasi pelaksanaan Pendidikan karakter dalam PAI di SMP Islam Al Amjad Medan meliputi: input (masukan), process (proses), output (hasil), dan outcomes (dampak). Input pelaksanaan (siswa maupun guru).